Social Policy and the Eurocrisis Quo Vadis Social Europe - Menz, Georg.; Menz, Georg.; Crespy, Amandine.; Crespy, Amandine. (Palgrave Studies in European Union Politics,, 2015)
In this study, an international and multidisciplinary team take stock of the promise and shortfalls of 'Social Europe' today, examining the response to the Eurocrisis, the past decade of social policy in the image of the Lisbon Agenda, and the politics that derailed a more Delorsian Europe from ever emerging.